Cell differentiation in response to nutrient availability : the repressor of meiosis, RME1, positively regulates invasive growth in Saccharomyces cerevisiae - Hansson, Guy Robert, 1974- (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--University of Stellenbosch, 2003.